Antimicrobial Susceptibility Pattern of Bacterial Isolates from Raw and Frozen Chicken Meat - Upreti, Rhythm; Pandey, Ritika; Basnet, Sahasna; K.C., Prashanna; Shrestha, Angela (SXC Journal, 2025)
Quality control in meat is essential, as it carries the risk of different pathogenic bacteria affecting human health. The study aimed to evaluate raw and frozen chicken meat samples quantitatively and qualitatively. Five raw and 5 frozen chicken meat samples were collected from retail shops in Kathmandu valley to detect the presence of E. coli, Salmonella spp., Pseudomonas and Staphylococcus aureus. The isolates were also examined for multidrug resistance (MDR) and phenotype detection of methicillin-resistant Staphylococcus aureus (MRSA). The total plate count for raw chicken was too high in all the samples, while that of frozen chicken meat was 2.3 x 10⁶ cfu/ml. The total coliform count and total fecal coliform count ranged from 5.7 x 10⁴ to 4.7 x 107 cfu/ml, and 1.01 x 10² to 1.12 x 10² cfu/ml, respectively. Among different isolates, Escherichia coli was detected in all 10 samples and most of the isolates (i.e. 70 %) were found to be resistant to the antibiotics ciprofloxacin. Similarly, Salmonella was present in 8 out of 10 (80%) samples, where 37.5% of isolates were found to be resistant toward azithromycin and ceftazidime. Staphylococcus aureus was identified in 6 samples, with all isolates showing resistance to ampicillin and cefoxitin (100%). Out of a total of 24 bacteria isolated, 7 (29.16%) exhibited multi-drug resistance; one isolate was E. coli and the remaining were Staphylococcus aureus. The results of this study showed the presence of potential human pathogens. These findings emphasize the critical need to enhance quality control and quality assurance systems in meat shops across the Kathmandu valley, ensuring public health safety.